Genetic and morphologic identities of hydrozoans (Cnidaria, Hydrozoa) from reef patches of Santa Marta, Colombian Caribbean - Torres-Rodríguez, Javier; Ortiz-Oyola, Daniel; Puentes-Sayo, Alejandra; Lecompte, Orlando P.; Jauregui, Aminta (Zootaxa, 2020)
The morphological and genetic identification of hydrozoans collected in the reef patches of Santa Marta, Colombia was carried out. This study allows to present two new records of hydroids species for the Colombian Caribbean: Halopteris alternata and Dentitheca dendritica. A total of 11 species and 1 genus were found using morphological and genetic identification with partial sequences of the mitochondrial 16S rRNA gene. The order Leptothecata was the most abundant represented by 9 families: Aglaopheniidae, Clytiidae, Haleciidae, Halopterididae, Kirchenpaueriidae, Plumulariidae, Sertularellidae, Sertulariidae and Thyroscyphidae, while the order Anthoathecata was represented by 2 families: Eudendriidae and Pennariidae. Despite the lack of studies on this group of organisms in the country, the use of the 16S rRNA gene proved to be very useful to provide complementary evidence in our understanding of the biological diversity of hydrozoans in Colombia.